Cognitive performance effects following a single dose of the M1 muscarinic positive allosteric modulator VU319: Human/Human trials: Cognitive enhancement. (7th December 2020) - Conley, Alexander C.; Key, Alexandra P.; Blackford, Jennifer U.; Rook, Jerri M.; Conn, Jeffrey; Lindsley, Craig W.; Jones, Carrie K.; Newhouse, Paul A.
Abstract: Background: VU319 is an investigational positive allosteric modulator of the M1 muscarinic acetylcholine receptor developed for cognitive enhancement in Alzheimer's disease (AD) and other disorders. Cognitive tasks including test of attention, speed, and memory and event‐related potentials (ERPs) were used during the double‐blind, placebo controlled Single Ascending Dose (SAD) study of VU319. The main pharmacodynamic objectives of the SAD were to identify early markers of functional engagement. Following the ascending dose cohorts, a Food Effect substudy was conducted to assess whether there was any change in the cognitive performance if VU319 was dosed with food compared to in a fasted state. Method: VU319 was given orally to 52 healthy volunteers aged 18‐55 years. The SAD study tested 40 participants in five dose escalating cohorts (60‐600 mg), in which 6 received VU319 and 2 received placebo. The Food Effect substudy consisted of 12 participants, in which ten received oral VU319 and two received placebo. Cognitive and electrophysiological tasks testing attention, memory and psychomotor speed were examined pre‐dosing and at 5 hours post‐dose. The tasks were selected for their sensitivity to cholinergic tone. Result: Single dose treatment showed improvements in cognitive and ERP performance on the higher doses of VU319 compared to placebo. Participants responded significantly faster to targets on the continuous performance test after 600 mg compared to placebo (p = 0.03, effect size d = 1.2). On the incidental memory task, participants who received 400 and 600 mg VU319 exhibited larger P300 amplitudes compared to placebo, when present with repeated compared to novel images (d > 0.8). Examination of the relationship between plasma levels of VU319 and cognitive performance showed that response time of psychomotor speed measures improved with increasing blood concentration of VU319 across doses (r>0.38). Conclusion: We conclude that these results demonstrate likely enhancement of the cholinergic system functioning in healthy adults following a single oral dose of VU319. These results provide an indication of the potential measures that are sensitive to cognitive activity by M1 allosteric modulators and provide a framework to examine the cognitive impact of multiple doses of VU319 in AD patients.